Identifying Social Roles in a Local Government’s Digital Community - Ali Saip, Mohamed; A. Kamala, Mumtaz; Tassabehji, Rana (International Journal of Engineering and Technology, 2018)
Social media have become an important interaction channel between the government and citizens in the era of the digital community. The adoption of social media in local government services offers a new channel to encourage citizen engagement in the public policy decision-making process. Moreover, communication with citizens through social media exposes large opportunities for the local government to analyse and appreciate the relationships among social media participants in the digital community to enhance public services. The purpose of this study is to understand the local government’s social media network and identify the social role in the local government’s social media network structure. Thus, this study adopted the social network analysis (SNA) approach on the Twitter data of a local government’s official account in the UK as a case study. The study revealed that the internal local government stakeholders play an important social role in the local government’s social media network. The implication of the study was discussed.